Differential regulation of heparan sulfate biosynthesis in fibroblasts cocultured with normal vs. cancerous prostate cells - Grigorieva, Elvira V.; Strokotova, Anastasia V.; Ernberg, Ingemar; Kashuba, Vladimir I. (Frontiers in Immunology, 2024)
Heparan sulfate proteoglycans (HSPGs) regulate a wide range of biological activities in both physiological and pathological conditions. Altered expression or deregulated function of HSPGs and their heparan sulfate (HS) chains significantly contribute to carcinogenesis as well and crucially depends on the functioning of the complex system of HS biosynthetic/modifying enzymes termed as "GAGosome". Here, we aimed at investigating the expression profile of the system in a cell culture model of stroma-epithelial crosstalk and searching for transcription factors potentially related to the regulation of expression of the genes involved. Coculture of BjTERT-fibroblasts with normal PNT2 human prostate epithelial cells resulted in significant downregulation (2-4-fold) of transcriptional activity of HS metabolism-involved genes (EXT1/2, NDST1/2, GLCE, HS2ST1, HS3ST1/2, HS6ST1/2, SULF1/2, HPSE) in both cell types, whereas coculture with prostate cancer cells (LNCaP, PC3, DU145) demonstrated no significant interchanges. Human Transcription Factor RT 2 Profiler PCR array and manual RT-PCR verification supposed FOS, MYC, E2F, SRF, NR3C1 as potential candidates for regulation and/or coordination of HS biosynthesis. Taken together, transcriptional activity of HS biosynthetic system in normal fibroblasts and prostate epithelial cells during their coculture might be controlled by their intercellular communication, reflecting of adaptation of these cells to each other. The regulation is attenuated or abrogated if normal fibroblasts interact with prostate cancer cells making the cancer cells independent of the limiting effects of fibroblasts, thus contributing to possibility of unlimited growth and progression. Overall, these data demonstrate an ability of cell-cell interactions to affect transcriptional activity of HS biosynthesis-involved genes.